Determinants of Organizational Citizenship Behavior on the Influence of Personality Traits on Leadership Style of Public Sector Officials in Riau Province: A Gender Perspective Review - Devi Alviani; Ririn Handayani; Hadiyati Hadiyati (Jurnal Psikologi Teori dan Terapan, 2023)
This research aimed to find out the determination of organizational citizenship behavior on the relationship between personality traits and leadership styles. The sample in this research is 234 respondents from 1.080 population, filled by the leader of Riau province public sector. Quantitative method used in this research. This research used probability sampling technique, proportional stratified random sampling method, and the Krejcie and Morgan, 1970 formula. The verification analysis technique of this research was carried out with statistical tests of Structural Equation Modeling (SEM) and Analysis of Moment Structure (AMOS) as analysis tools. This research shows that: openness to experience has a positive and significant effect on leadership style; neuroticism has a positive and significant effect on leadership style; organizational citizenship behavior is a quasi-moderating between openness to experience and leadership style positively and significantly; and organizational citizenship behavior is a quasi-moderation on the between neuroticism and leadership style negative and significantly. Penelitian ini dilaksanakan pada Sektor Publik Provinsi Riau dengan tujuan mengetahui determinan organizational citizenship behavior pada hubungan personality traits dan gaya kepemimpinan pejabat. Kuantiitatif digunakan sebagai pendekatan pada penelitian ini. Pengambilan sampel dilakukan dengan teknik sampling Probability, metode Proportionate Stratified Random Sampling dengan formula Krejcie and Morgan, 1970 dari 1.080 populasi menjadi 234 responden. Teknik analisa verifikatif penelitian ini dilakukan dengan uji statistic Structural Equational Modelling (SEM) dan Analysis of Moment Structure (AMOS) sebagai alat analisisnya. Hasil analisis membuktikan variabel openness to experience berpengaruh positif signifikan terhadap gaya kepemimpinan; variabel neuroticism berpengaruh positif signifikan terhadap gaya kepemimpinan; variabel organizational citizenship behavior merupakan quasi moderasi pada hubungan openness to experience dan gaya kepemimpinan secara positif signifikan; dan variabel organizational citizenship behavior merupakan quasi moderasi pada hubungan neuroticism dan gaya kepemimpinan secara negatif signifikan.